2005
DOI: 10.1523/jneurosci.4476-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Activity-Dependent Plasticity at Corticostriatal Synapses

Abstract: Corticostriatal projections originate from the entire cerebral cortex and provide the major source of glutamatergic inputs to the basal ganglia. Despite the importance of corticostriatal connections in sensorimotor learning and cognitive functions, plasticity forms at these synapses remain strongly debated. Using a corticostriatal slice preserving the connections between the somatosensory cortex and the target striatal cells, we report the induction of both non-Hebbian and Hebbian forms of long-term potentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
267
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(294 citation statements)
references
References 50 publications
22
267
3
Order By: Relevance
“…This finding is in agreement with the current model of a functional network that modulation of synchrony is a mechanism of dynamic network reconfiguration (Womelsdorf et al, 2007). Mechanisms underlying the beta dynamics could be a frequency transition of oscillatory circuits through synaptic coupling alterations (Kopell et al, 2000;Jensen et al, 2005), changes in nonsynaptic coupling through gap junction conductance in cortical neurons (Roopun et al, 2006), and synaptic plasticity in cortico-striatum connections (Fino et al, 2005). The latter is particularly interesting in that the striato-thalamo-cortical circuit is involved in coincidence detection of oscillatory activities for temporal coding (Matell and Meck, 2004).…”
Section: Dissociation Between Beta Suppression and Reboundsupporting
confidence: 90%
“…This finding is in agreement with the current model of a functional network that modulation of synchrony is a mechanism of dynamic network reconfiguration (Womelsdorf et al, 2007). Mechanisms underlying the beta dynamics could be a frequency transition of oscillatory circuits through synaptic coupling alterations (Kopell et al, 2000;Jensen et al, 2005), changes in nonsynaptic coupling through gap junction conductance in cortical neurons (Roopun et al, 2006), and synaptic plasticity in cortico-striatum connections (Fino et al, 2005). The latter is particularly interesting in that the striato-thalamo-cortical circuit is involved in coincidence detection of oscillatory activities for temporal coding (Matell and Meck, 2004).…”
Section: Dissociation Between Beta Suppression and Reboundsupporting
confidence: 90%
“…Such rules have first been described in mormyrid electric fish (36) where they explain the formation of negative mirror images (corollary discharges) of reafferent (self-generated) sensory input (2). In mammals, a similar rule has been found to describe synaptic connections from cortex to the basal ganglia (37). Thus, a causal inverse may reside in the efferent synapses of a cortical area upstream of the basal ganglia homolog; or, based on anatomy, a causal inverse could be connected to a dopaminergic ventral tegmental area (38,39), thereby establishing a possible link of our findings with reinforcement learning theories (see below).…”
Section: Discussionsupporting
confidence: 76%
“…On the other hand, the results of ref. 37 reveal that afferent cortical synapses onto striatal neurons also exhibit plasticity in which postsynaptic before presynaptic firing strengthens the synapse, a rule useful for inverse model learning, according to the theory of refs. 23 and 24.…”
Section: Discussionmentioning
confidence: 99%
“…In the striatum, however, the results obtained to date seem contradictory. Fino et al (2005) reported that spike-timedependent LTD (t-LTD) was induced when presynaptic spikes preceded postsynaptic spikes (pre-post timing), and reversed timing (post-pre timing) produced long-term potentiation (t-LTP). In contrast, Pawlak and Kerr (2008) found that pre-post timing caused t-LTP and reverse timing caused t-LTD. Shen et al (2008) found that pre-post protocols produced t-LTP in dopamine D1 receptorexpressing cells, but under dopamine-depleted conditions, D1 cells showed LTD.…”
Section: Introductionmentioning
confidence: 99%